Do Financial Incentives for Training and Caseworker Meetings Enhance Re-Employment? - Tomi Kyyrä; Jouko Kullervo Verho (Institute of Labor Economics (IZA), 2025)
In 2005, displaced workers in Finland with at least three years of work history were given the option to enroll in a Re-employment Program. Participants met with a caseworker at the beginning of their unemployment and drafted an employment plan. In return, they became eligible for higher benefits for four weeks, as well as for the duration of individually targeted training programs specified in their plan. The program aimed to provide early counseling, encourage participation in labor market training, and improve matches between training programs and job seekers. Using a difference-in-differences approach, we show that the program increased caseworker meetings and participation in training programs but had no effect on unemployment duration in the short run or employment in the longer run. The effect on training participation was particularly strong for men, older workers and low-skilled workers, yet unemployment and employment effects were equally disappointing across all subgroups.
Keywords: C21; J64; J68; 330; active labor market policy; re-employment; caseworkers; unemployment benefits; labor market training